Innovation Agencies : Cases from Developing Economies - Aridi, Anwar; Kapil, Natasha (World Bank, Washington, DC, 2019)
Many high-income and developing countries have established agencies to promote innovation. This study examines the origin and evolution, organizational structure, policy interventions, delivery challenges, and evaluation mechanisms of 13 innovation agencies in developing countries and one case (SPRING in Singapore) for comparison purposes. This study does not assume that the only approach to improving innovation lies in a dedicated agency – each innovation system is governed differently and the same intervention may have very different results in different contexts. Rather, our goal is to capture how these agencies dealt with the major challenges that confront establishing an innovation agency in a developing country context, where innovation is often hampered by significant market, coordination, and institutional failures, investments in innovation tend to be limited, and the capabilities required for effective innovation are often lacking. The analysis is presented according to seven building blocks that emerged from the analysis of the cases’ patterns and dynamics as pre-requisites for the success of innovation agencies, including a clear but adaptable mission, capable staff, effective governance and management structures, diagnostic-based interventions, robust monitoring and evaluation (M&E), sustainable funding, and strategic partnerships and networks. A diagnosis of NIS gaps and global trends is required to design policy interventions.